이동원 음화론이 후대 내상병 치료에 미친 영향 - 신진봉(Jin Bong Shin); 이재원(Jae Won Lee); 전지영(Ji Young Jeon); 전용철(Yong Cheol Jeon); 문구(Goo Moon); 원진희(Jin Hee Won) (동의생리병리학회지, 2008)
According to a treatment of internal disease in oriental medicine, we recognize that Lee Dong-won's Eumhwalon has a critical meaning. However, there is no well organized study about that so far even though medical treatments and prescriptions affected by Lee Dong-won's Eumhwalon have been used in clinical medicine. Hence I have studied the effect on a treatment of internal disease of after age affected by Lee Dong-won's Eumhwalon focused on medical treatments and prescriptions. For the comprehensive study on the effect of Lee Dong-won’s(李東垣) Eumwhalon(陰火論) on a treatment of internal disease for after age, I have examined, collected, and summarized the related descriptions from various books and papers in this subject such as <Naek-yung(內經)> which is the bible of oriental medicine. Followings are obtained as a result: Lee dong-won said Eumhwa(陰火) might be happened if there are abnormalities of the spleen and the stomach which exercise going up and coming down(升降). Lee dong-won offered Gamonjeyol(甘溫除熱) and Sengyangsanwha(升陽散火) as treatments of Eumhwa(陰火) Gamonjeyol(甘溫除熱) affected the treatment and the pathological recognition of Daekilon(大氣論) by Jang suk-sun(張錫純). Consequently there are some prescriptions such as Sengham-tang(升陷湯), Wandae-tang(完帶湯), Kerwonjern(擧元煎), and so on affected by Gamonjeyol(甘溫除熱). Sengyangsanwha(升陽散火) affected Yuklumanju(逆流挽舟) by Yu chang(喩昌) a lot. It is a meaning of Sengyangsanwha(升陽散火) that he used Insampaedok-san(人蔘敗毒散) to dysentery. As a representative prescription, there are Insampaedok-san(人蔘敗毒散), Kamisoyo-san(加味逍遙散), Baekchuljakyak-san(白朮芍藥散), and so on.